1989
DOI: 10.2176/nmc.29.55
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Vertebral Arteriovenous Fistulas and Atlantoaxial Dislocation associated with Neurofibromatosis

Abstract: The authors report a rare case involving neurofibromatosis associated with bilateral vertebral arteriovenous fistulas and atlantoaxial dislocation. Multiple neurofibromas in the craniocervical junc tion appeared to be the cause of the atlantoaxial dislocation in this patient, and the dislocation might have contributed to the formation of the bilateral vertebral arteriovenous fistulas. The fistulas were suc cessfully treated by a combination of balloon embolization and surgery followed by occipitocervical fu si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…reported a case of NF similar to the subject of the present paper with bilateral vertebral arteriovenous fistulas and atlantoaxial dislocation. However, the treatment in this case was carried out by combined surgical and endovascular means 8 . Our patient was treated by endovascular technique alone.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…reported a case of NF similar to the subject of the present paper with bilateral vertebral arteriovenous fistulas and atlantoaxial dislocation. However, the treatment in this case was carried out by combined surgical and endovascular means 8 . Our patient was treated by endovascular technique alone.…”
Section: Discussionmentioning
confidence: 85%
“…The patient was treated successfully with endovascular treatment in the form of embolization of bilateral fistulas with balloons and coils. A review of the published literature reveals only one similar case of bilateral vertebral arteriovenous fistulas in NF1 reported previously 8 .…”
Section: Introductionmentioning
confidence: 96%
“…Multiple neurofibromas in the craniocervical junction appeared to be the cause of the atlantoaxial dislocation in this patient, and the dislocation might have contributed to the formation of the bilateral vertebral arteriovenous fistulas. Hasegawa H et al 5 reported a similar case in which there was presence of vertebral artery and vein fistula in the setting of neurofibromatosis and atlantoaxial dislocation. We feel that the present case might be similar to this extremely rare condition.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of myelopathy in VVAVFs can result from direct spinal cord compression from epidural venous engorgement, and/or venous hypertension from pial venous reflux [18,26]. Undoubtfully, the mechanism of severe cervical cord compression in our with resolution of cervical cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…case can occur from forceful epidural compression from bilateral dilated epidural venous pouches. The large epidural venous pouch compressing spinal cord from spontaneous VVAVF was found more frequently in the fistula associated with NF1 [21,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%